Candida auris Outbreak in a Multidisciplinary Hospital in Romania during the Post-Pandemic Era: Potential Solutions and Challenges in Surveillance and Epidemiological Control - Violeta Melinte; Alexandra Daniela Tudor; Adrian Georgian Bujoi; Maria-Adelina Radu; Maria Cristina Văcăriou; Ioana Miriana Cismaru; Tiberiu Sebastian Holban; Carmen Luminița Mîrzan; Ruxandra Popescu; Robert Cătălin Ciupan; Alin Baciu; Oriana Elena Moraru; et al. (MDPI AG, 2024)
Candida auris is a newly emerging yeast, which is raising public health concerns due to its outbreak potential, lack of protocols for decontamination and isolation of patients or contacts, increased resistance to common antifungals, and associated high mortality. This research aimed to describe the challenges related to identifying the outbreak, limiting further contamination, and treating affected individuals. We retrospectively analyzed all cases of C. auris detected between October 2022 and August 2023, but our investigation focused on a three-month-long outbreak in the department of cardio-vascular surgery and the related intensive care unit. Along with isolated cases in different wards, we identified 13 patients who became infected or colonized in the same area and time, even though the epidemiological link could only be traced in 10 patients, according to the epidemiologic investigation. In conclusion, our study emphasizes the substantial challenge encountered in clinical practice when attempting to diagnose and limit the spread of an outbreak. Therefore, it is crucial to promptly apply contact precaution measures and appropriate environmental cleaning, from the first positive case detected.